INTRODUCTORY ORGANIC CHEMISTRY AND HYDROCARBONS : a physical chemistry approach. - Lima Firme, Caio. ([Place of publication not identified] : CRC PRESS, 2019)
A novel proposal for teaching organic chemistry based on a broader and simplified use of quantum chemistry theories and notions of some statistical thermodynamic concepts aiming to enrich the learning process of the organic molecular properties and organic reactions. A detailed physical chemistry approach to teach organic chemistry for undergraduate students is the main aim of this book. A secondary objective is to familiarize undergraduate students with computational chemistry since most of illustrations of optimized geometries (plus some topological graphs) and information is from quantum chemistry outputs which will also enable students to obtain a deeper understanding of organic chemistry.
OCLC-licensed vendor bibliographic record.
Keywords: Chemistry, Organic; Hydrocarbons; SCIENCE / Chemistry / Organic; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Life Sciences / General